Potential Adverse Effects of Violent Video Gaming: Interpersonal- Affective Traits Are Rather Impaired Than Disinhibition in Young Adults - Kimmig, Ann-Christin S.; Andringa, Gerda; Derntl, Birgit (Frontiers in Psychology, 2018)
The increasing trend of mass shootings, which were associated with excessive use of violent video games, fueled the debate of possible effects violent video games may have on adolescents and young adults. The aim of this study was to investigate the possible link between violent video gaming effects and the disposition of adverse behavior traits such as interpersonal-affective deficits and disinhibition. Data of 167 young adults, collected by an online questionnaire battery, were analyzed for lifetime video game exposure differences (i.e. non-gamers, non-violent video gamers, stopped violent video game users and ongoing violent video game users) as well as for recent exposure effects on adverse behavior traits (Levenson’s Psychopathy Scale), while controlling for other potentially confounding lifestyle factors. While interpersonal-affective deficits were significantly higher in participants with ongoing violent video game exposure compared to non-gamers and non-violent video gamers, disinhibition was significantly higher in both – stopped and ongoing – violent video game exposure groups compared to non-gamers. Recent violent video-game exposure was a stronger predictor for interpersonal-affective deficits, but was also significant for disinhibition. Considering that we observed small to medium effects in a sample of young adults with little to moderate use of violent video games highlights the importance of further investigating the potential adverse effects of violent video games on quality of social relationships.